Oncogenic Ras and ΔNp63α cooperate to recruit immunosuppressive polymorphonuclear myeloid-derived suppressor cells in a mouse model of squamous cancer pathogenesis - Sakakibara, Nozomi; Clavijo, Paúl E.; Sievers, Cem; Gray, Veronica C.; King, Kathryn E.; George, Andrea L.; Ponnamperuma, Roshini M.; Walter, Beatriz A.; Chen, Zhong; Van Waes, Carter; Allen, Clint T.; Weinberg, Wendy C. (Frontiers in Immunology, 2023)
Amplification of human chromosome 3q26-29, which encodes oncoprotein ΔNp63 among other isoforms of the p63 family, is a feature common to squamous cell carcinomas (SCCs) of multiple tissue origins. Along with overexpression of ΔNp63, activation of the protooncogene, RAS, whether by overexpression or oncogenic mutation, is frequently observed in many cancers. In this study, analysis of transcriptome data from The Cancer Genome Atlas (TCGA) demonstrated that expression of TP63 mRNA, particularly ΔNp63 isoforms, and HRAS are significantly elevated in advanced squamous cell carcinomas of the head and neck (HNSCCs), suggesting pathological significance. However, how co-overexpressed ΔNp63 and HRAS affect the immunosuppressive tumor microenvironment (TME) are incompletely understood. Here, we established and characterized an immune competent mouse model using primary keratinocytes with retroviral-mediated overexpression of ΔNp63α and constitutively activated HRAS (v-rasHa G12R) to evaluate the role of these oncogenes in the immune TME. In this model, orthotopic grafting of wildtype keratinocytes expressing both v-rasHa and elevated levels of ΔNp63α consistently yield carcinomas in syngeneic hosts, while cells expressing v-rasHa alone yield predominantly papillomas. We found that polymorphonuclear (PMN) myeloid cells, experimentally validated to be immunosuppressive and thus representing myeloid-derived suppressor cells (PMN-MDSCs), were significantly recruited into the TME of carcinomas arising early following orthotopic grafting of ΔNp63α/v-rasHa-expressing keratinocytes. ΔNp63α/v-rasHa-driven carcinomas expressed higher levels of chemokines implicated in recruitment of MDSCs compared to v-rasHa-initiated tumors, providing a heretofore undescribed link between ΔNp63α/HRAS-driven carcinomas and the development of an immunosuppressive TME. These results support the utilization of a genetic carcinogenesis model harboring specific genomic drivers of malignancy to study mechanisms underlying the development of local immunosuppression.